PATH-25. SURVIVAL STRATIFICATION OF IDH MUTANT GLIOMA USING METHYLATION AND mRNA ANALYSIS OF HOX GENES - Mamatjan, Yasin (Neuro Oncol, 2018)
Diffuse gliomas are separated based on IDH mutation (mut) status. However, IDH-mut gliomas manifest wide range of clinical outcome that are not explained by the current genomic classification. We aim to identify clinically and biologically relevant subgroups within IDH-mut low grade gliomas to gain a deeper insight and improve classification. We used 412 IDH-mut gliomas profiled by The Cancer Genome Atlas (TCGA) Network, utilising methylation, mRNA and mutation datasets to identify unique molecular signatures. We found that IDH-mut gliomas further subdivide into 2 groups based on mutational rate. High mutation load predicts poor survival in IDH-mut glioma. Analysis of differentially expressed genes in high versus low-mutational rate showed significant enrichment of HOX genes, 24/40 HOX genes were up regulated in this group. Interestingly, both overexpression and hyper-methylation of specific HOX genes were associated with worse survival. We further show that 7 of these HOX genes (HOXA4, HOXA7, HOXA10, HOXA13, HOXD3, HOXD9, and HOXD10) are the most significant in determining survival. Signed average of 7 Hox genes significantly improved survival and hazard ratio (HR) based on high versus low methylation (HR=4.3, p<0.0001) and high versus low mRNA expression (HR=2.8, p=0.00095). Similarly, effect on survival based on high expression and hyper-methylation of HOX genes was not only observed in IDH-mut 1p/19q-codeleted and non-codeleted groups independently, but also in IDH-wild-type low grade glioma. Multivariate analysis adjusted for confounding factors (grade, age and codeletion status) showed prognostic factors associated with survival in high versus low methylated group (HR=3.2, p=0.0036). Interestingly, only the same direction (high-high and low-low groups) of both mRNA and methylation showed significance and increased HR, which challenges the current understanding of methylation of genes and gene expression. We show that IDH-mut gliomas can further be stratified into clinically relevant categories based on high mRNA expression and hyper-methylation of Hox genes.